Layanan Konseling Kelompok Dengan Pendekatan Behavioral Contract Untuk Meningkatkan Motivasi Belajar Siswa - Marfu’atun, Marfu’atun; Yulianti, Dewi; Hasanah, Maulidatul (Jurnal Bimbingan dan Konseling Borneo, 2024)
The type of research was quantitative research. The purpose of the quantitative approach was to obtain research results expressed in the form of numbers that were explained using statistical formula. This research aims to examine the improvement in student learning motivation through group counseling services using a behavioral contract approach. The type of research was quasi-experimental with a research design of one group pre-test and post-test. Based on the data analysis using a t-test, it shows that the t-value is greater than the t-table (20.79 2.571) at a significance level of 5%, indicating that there is an influence of group counseling services with a behavioral contract approach to improve the learning motivation of  VIIID grade students at SMPN 2 Masbagik. This indicates that Ha (the alternative hypothesis) is accepted, and Ho (the null hypothesis) is rejected. Therefore, it can be concluded that there is an influence of group counseling services with a behavioral contract approach to improve the learning motivation of  VIIID grade students at SMPN 2 Masbagik